ANTIOXIDANT ENZYMES CAPACITY IN PATIENTS WITH RHEUMATOID ARTHRITIS: THE RELATIONSHIP WITH DISEASE ACTIVITY SCORE - Kadir Yıldırım,; Saliha Karatay,; Gürhan Güreser,; Ahmet Kızıltunç,; Mahir Uğur,; Kazım Şenel, (Archives of Rheumatology, 2004)
The aims of this study were to check the alterations in serum levels of antioxidant enzyme activities and to assess whether the disease activity scores are reflected by serum antioxidant enzyme capacity in patients with RA. The levels of erythrocyte CuZn superoxide dismutase (CuZnSOD) and glutathione peroxidase (GSH-Px) were assessed in 20 patients with rheumatoid arthritis (RA) and 20 healthy control subjects. Disease activity score (DAS28) was calculated for all patients. Erythrocyte CuZnSOD activity levels in RA patients and control subjects were 13.8 ± 2.5 (U/mg. protein) and 8.62 ± 1.8 (U/mg. protein), respectively. There was a significant difference between the groups (p<0.001). The mean erythrocyte GSH-Px values were 27.6 ± 9.3 (µmol NADPH oxidized/min/mg.protein) and 14.5 ± 3.3 (µmolNADPH oxidized/min/mg.protein) for the RA patients and controls subjects, respectively. There was a significant difference with respect to erythrocyte GSH-Px activity values between the groups (p<0.001). The mean DAS 28 score in RA patients was 3.44 ± 1.23. There was a significant positive correlation between each of erythrocyte CuZnSOD and GSH-Px levels and DAS28 scores for the RA patients (r= 0.80, p<0.001; r= 0.81, p<0.001 respectively). Positive correlation between erythrocyte CuZnSOD and GSH-Px activity values and CRP (r=0.68, p<0.001; r=0.76, p<0.001), was not detected with ESR. The present study indicated that increased erythrocyte CuZnSOD and GSH-Px levels that might play a role in the tissue damage and inflammation process of this disease may be a useful marker for evaluating of the disease activity in patients with RA.